서울시 정수장의 THMs 생성과 관련된 한강 원수의 주요 수질 특성 조사 - 이진효(Jin Hyo Lee); 이기선(Ki Seon Lee); 황동연(Dong Hyun Hwang); 이만호(Man Ho Lee); 한선희(Sun Hee Han); 박용상(Yong Sang Park); 이목영(Mok Young Lee); 이진숙(Jin Sook Lee); 구자용(Ja Yong Koo) (Daehan hwan'gyeong gonghag hoeji, 2011)
In a study on THMs formation at the distribution facilities in Seoul water supply for past 3 years from 2007 to 2009, THMs production was increased from inlet to outlet during the process in water treatment plant. However, such increased THMs amount was very small compared to THMs production formed after pre-chlorination and post chlorination. Accordingly, this study is aimed to investigate the characteristics of water quality parameters of Han River related to THMs formation in 6 water treatment plants in Seoul. The results showed that THMs and other factors such as temperature (r = 0.539~0.846) and turbidity (r = 0.421~0.863) had positive correlation while THMs had negative correlation with pH (r = -0.613~-0.800) and algae (r = -0.582~-0.901). There is no correlation between THMs and $NH_3-N$. According to the factor analysis, generally metabolite and organic matter factor $X_1$ (pH, BOD, algae), and seasonal and natural factor $X_2$ (temperature, turbidity) played an important role in the formation of THMs. Multiple regression analysis for THMs formation showed significance of regression appeared in most water systems. 2007년에서 2009년까지 3년간 서울시 급수과정별 시설에서의 THMs 생성특성 조사에서, 정수장 이후의 급수과정별 시설 즉, 배수지 전 후, 유입부, 가압장, 관말지역으로 갈수록 THMs 생성량은 증가하였지만 그 증가량은 전염소처리 및 후염소처리 후 정수지 체류과정에서 이미 생성된 THMs량에 비해 작은 것으로 나타났다. 따라서 본 연구에서는 서울시 6개 정수장의 THMs 생성 특성 및 영향인자인 정수장 송수잔류염소, 한강 원수의 여러 수질항목 특성을 조사하였다. 6개 정수장 전체자료(n = 72)에 대하여 THMs와 다른 항목간의 상관성 분석결과, 수온(r = 0.539~0.846), 탁도(r = 0.421~0.863)는 양(+)의 상관성을, pH (r = -0.613~ -0.800), 조류(r = -0.582~ -0.901)는 음(-)의 상관성을 갖는 것으로 나타났으며, 원수의 $NH_3-N$는 THMs와의 상관성이 크게 없는 것으로 나타났다. 또한 요인분석을 실시한 결과, 전반적으로 물질대사 및 유기물 관련 요인 $X_1$ (pH, BOD, 조류), 계절적 자연적 변동요인 $X_2$(수온, 탁도)가 다른 항목들에 비해 정수장에서의 THMs 생성에 영향을 미치는 것으로 나타났다. 또한 THMs에 대한 다중회귀분석을 실시한 결과, 일부 수계를 제외한 다른 모든 수계에서 회귀식의 유의성을 확인할 수 있었다.